Tanggung Jawab Pelaku Usaha terhadap Konsumen Go Food dalam Transaksi E-Commerce - I Putu Wisna Dana; Ni Luh Made Mahendrawati; Ni Gusti Ketut Sri Astiti (Warmadewa Press, 2020)
Economic transactions have been integrated with internet technology which is often called e-commerce. Although it has been arranged in such a way to protect the rights of consumers, the use of standard agreements in e-commerce transactions still has the risk of large losses to consumers. Based on the background of the problems above, this research was conducted with the aim of elaborating the responsibilities of business actors to consumers in the event of default in the Go Food transaction using e-commerce and describing sanctions for Go Food businesses that apply fraudulent use of e-commerce. Referring to the formulation of the problem, this study was designed using a normative research approach. The method used in the processing of legal materials, namely analytical descriptive data analysis methods. In accordance with the results of data analysis, the responsibility of business operators for defaults in Go Food transactions using e-commerce was to return Go-Pay balances. Sanctions for Go Food businesses that apply cheating in using e-commerce, which result in losses to consumers, were not only limited to the dismissal of partners, but sanctions could also be imposed on irresponsible business actors. The sanctions in question could be in the form of civil, criminal or administrative sanctions.